2001
DOI: 10.1007/s002470000398
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of hypochondroplasia: the role of radiological interpretation

Abstract: Our study shows that the crucial skeletal regions on which to focus the diagnosis of hypochondroplasia are the lumbar spine and legs, while the pelvis and hands seem to be less characteristic. To reduce the risk of misdiagnosis, accurate radiological and clinical evaluation is needed, especially in cases without a defined genetic defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Clinical Study I Flechtner and others Impact of skeletal dysplasia on growth ossification; and the pelvis for iliac wings, shortness of the femoral necks, and metaphyseal and epiphyseal anomalies (21,32,33,34). All radiographs were read by a panel of specialists including geneticists from the French reference center for skeletal dysplasia, radiologists, and pediatric endocrinologists.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Clinical Study I Flechtner and others Impact of skeletal dysplasia on growth ossification; and the pelvis for iliac wings, shortness of the femoral necks, and metaphyseal and epiphyseal anomalies (21,32,33,34). All radiographs were read by a panel of specialists including geneticists from the French reference center for skeletal dysplasia, radiologists, and pediatric endocrinologists.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Clinical severity in HCH has been attributed to having the FGFR3 mutation [Rousseau et al, 1996]. Such phenotypic and genotypic heterogeneity complicates the diagnosis of HCH [Prinster et al, 2001]. Such heterogeneity prompted us to investigate other genetic mutations in the causation of the HCH phenotype.…”
Section: Introductionmentioning
confidence: 98%
“…The variable and mild manifestations of hypochondroplasia make it difficult to establish a precise diagnosis of the disorder on clinical grounds prior to and even after birth (Hall and Spranger, 1979;Lachman, 1996;Prinster et al, 2001). Jones et al reported a sporadic patient who was prenatally suspected as having a shortlimb skeletal dysplasia and was diagnosed as hypochondroplastic one year after birth (Jones et al, 1990).…”
Section: Introductionmentioning
confidence: 99%